THE ROLE OF ZINC SULPHATE AND OMEGA 3 IN IMPROVING OF ALBUMIN LEVEL ON PULMONARY TUBERCULOSIS PATIENTS IN PARU HOSPITAL SURABAYA 2015 - Durry, Fara Disa; Wirjatmadi, Bambang (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2015)
The epidemiology of Tuberculosis (TB) showed that TB is a disease which is associated with malnutrition. Malnutrition and lacking of certain essential nutrients required by immune system might cause immune function deficiency resulting higher susceptibility to bacterial and viral infections. There is positive correlation between immune system and high nutrient contents, such as Vitamin C, zinc, and antioxidants that brings good effect on infections, including Tuberculosis. One of the efforts conducted to help promoting improving albumin level on pulmonary tuberculosis patients is through zinc and sulphate provision followed by Omega-3 supplementation. This study was conducted in 2015 aimed to analyze the role of Zinc Sulphate Omega-3 provision in improving albumin level on pulmonary tuberculosis patients in Paru Hospital, Surabaya.This study applied randomized study design using Pre-test and Post-test Control group design on patients suffering pulmonary tuberculosis. This study was conducted by administering Zinc Sulphate and Omega-3 on treatment group and placebo on the control group. The samples of this study consisted of 20 pulmonary tuberculosis patients divided into two groups: treatment group and control group. Each group consisted of 10 patients. Statistical analysis was conducted using paired T-test and independent t-test. The results is There were significant differences in albumin level (p = 0.001) in the treatment group before and after supplementation Zinc Sulphate And Omega 3. While in the control group between before and after supplementation Zinc Sulphate And Omega 3 showed no significant differences in body weight (p = 0.224). The conclusions is Zinc Sulphate and Omega 3 plays a role in increasing albumin level respondents. There are significant differences on albumin level before and after supplementation Zinc Sulphate And Omega 3.